Development of Functional Academic Assessment Instruments for Students with Intellectual Disabilities Transition Program - Een Ratnengsih; Riksma Nurahmi Rinalti Akhlan; Astri Nursifa; Lulu Fikriyah Shalihat; Fauzia Putri Awalya (Department of Special Education, 2021)
The phase transition from formal education to living in society for students with intellectual disabilities still leaves many problems. At the high school level, academic learning should support the skills given to students with intellectual disabilities during the transition period. Assessment is an important part that a teacher must carry out before preparing a lesson plan. A qualified assessment instrument will help teachers in the process of finding student learning needs. This study aims to develop a functional academic assessment instrument that is valid and practical to support data collection for learning purposes. The development model used is the ADDIE model with the Analyze, Design, Develop, Implement, Evaluate stages. The results showed that the assessment instruments in the functional academic field consisted of the aspects of reading, writing, and arithmetic accompanied by guidelines for their use. The results of expert validation and product practicality tests carried out on the developed instruments are categorized as very valid, practical, and effective. Therefore, the instrument can be used as a guide in assessing learning needs in transition programs for students with intellectual disabilities.